Nurse practitioner model of care for the initiation of pre‐exposure prophylaxis: A case series study. Issue 2 (27th September 2022) - Cornelius, Judith B.; Gunn, Laura H.; Dalton, Cynthia; Davis, Bernard
Abstract: Aim: The purpose of this study was to create and implement a nurse practitioner model of care in the initiation of a pre‐exposure prophylaxis (PrEP) protocol with African American men who have sex with men (MSM). Design: A case series design was used to implement the protocol for a nurse practitioner PrEP‐based model of care. Methods: The participatory, evidence‐based, patient‐focus process (PEPPA) framework and the American Association of Colleges of Nursing (AACN) Doctoral Essentials for Advanced Practice were aligned to guide the development, implementation, and evaluation of this advanced practice role in an urban medical clinic. Results: Seven African American HIV‐negative MSM who received treatment under the nurse practitioner PrEP‐based model of care had increased PrEP knowledge and medication adherence and did not contract a sexually transmitted infection. Conclusions: New models of care can be created to meet the Getting to Zero HIV initiative of reducing rates of HIV infections with MSM.